1999
DOI: 10.1016/s0014-5793(99)00331-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human uncoupling protein‐3 increases thermogenesis in yeast cells

Abstract: The long form of human uncoupling protein-3 (hUCP3L) is highly homologous to thermogenin (UCP1), the uncoupling protein of brown fat mitochondria, but is expressed predominantly in skeletal muscle. Its putative role is to regulate the coupling efficiency of oxidative phosphorylation and thus thermogenesis in skeletal muscle, a major thermogenic tissue in higher mammals. To study the functional relevance of hUCP3L, the protein was expressed in yeast cells under the control of the galactose promoter. Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 24 publications
6
57
0
2
Order By: Relevance
“…41 In our study, the observed reduction in mitochondria membrane potential after UCP2 gene transfer assessed by spectro¯uorometry could be con®rmed by FCM. A similar decrease was also obtained by FCM in yeast or myoblasts overexpressing UCP2 or UCP3 3,5,7,8,53,54 or even in adipocytes from transgenic mice overexpressing UCP1. 55 Moreover, we observed that GDP addition to mitochondrial preparations did not change mitochondria membrane potential analyzed by FCM, in muscles expressing UCP2 (data not shown), which is in agreement with recent reports.…”
Section: Effect Of Ucp2 Muscle Gene Transfer a Marti Et Alsupporting
confidence: 74%
“…41 In our study, the observed reduction in mitochondria membrane potential after UCP2 gene transfer assessed by spectro¯uorometry could be con®rmed by FCM. A similar decrease was also obtained by FCM in yeast or myoblasts overexpressing UCP2 or UCP3 3,5,7,8,53,54 or even in adipocytes from transgenic mice overexpressing UCP1. 55 Moreover, we observed that GDP addition to mitochondrial preparations did not change mitochondria membrane potential analyzed by FCM, in muscles expressing UCP2 (data not shown), which is in agreement with recent reports.…”
Section: Effect Of Ucp2 Muscle Gene Transfer a Marti Et Alsupporting
confidence: 74%
“…The present data indicate that UCP2, UCP3, StUCP and AtUCP alter the mitochondrial membrane potential recorded in i o in recombinant yeast and mammalian cells, and probably uncouple respiration [17,30,31,57,[59][60][61]84,85]. The respiration of isolated yeast mitochondria into which UCP2 had been introduced was less coupled than that of control mitochondria [30].…”
Section: Proton Transport Activity Of Ucp2 Ucp3 and Plant Ucps And mentioning
confidence: 57%
“…Measurements of UCP2 and UCP3 uncoupling activity. Using heterologous yeast and mammalian cell expression systems, UCP2 and UCP3 have been shown to reduce growth and decrease the mitochondrial membrane potential as measured by uptake of potential-sensitive fluorescent dyes (62, 74,75,87,[91][92][93]. Because qualitatively similar effects have been observed with UCP1 (75,87,94), uncoupling activity for UCP2 and UCP3 was suggested.…”
Section: Uncoupling Acitivity Of Ucp2 and Ucp3mentioning
confidence: 97%